Question
upstudy study bank question image url

Solve for \( x \) : 1. \( x-5=\frac{6}{x} \) 2. \( \frac{x^{2}-3 x-7}{x^{2}-x-2}=\frac{x+2}{x+1}-1 \) 3. \( \frac{2}{x}-\frac{x+1}{x+2}=1 \)

Ask by Dunn Burton. in South Africa
Feb 04,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solutions are: 1. \( x = -1 \) and \( x = 6 \) 2. \( x = 5 \) 3. \( x = \frac{-1 + \sqrt{33}}{4} \) and \( x = \frac{-1 - \sqrt{33}}{4} \)

Solution

Solve the equation \( x-5=\frac{6}{x} \). Solve the equation by following steps: - step0: Solve for \(x\): \(x-5=\frac{6}{x}\) - step1: Find the domain: \(x-5=\frac{6}{x},x\neq 0\) - step2: Multiply both sides of the equation by LCD: \(\left(x-5\right)x=\frac{6}{x}\times x\) - step3: Simplify the equation: \(x^{2}-5x=6\) - step4: Move the expression to the left side: \(x^{2}-5x-6=0\) - step5: Factor the expression: \(\left(x-6\right)\left(x+1\right)=0\) - step6: Separate into possible cases: \(\begin{align}&x-6=0\\&x+1=0\end{align}\) - step7: Solve the equation: \(\begin{align}&x=6\\&x=-1\end{align}\) - step8: Check if the solution is in the defined range: \(\begin{align}&x=6\\&x=-1\end{align},x\neq 0\) - step9: Find the intersection: \(\begin{align}&x=6\\&x=-1\end{align}\) - step10: Rewrite: \(x_{1}=-1,x_{2}=6\) Solve the equation \( \\frac{x^{2}-3x-7}{x^{2}-x-2}=\\frac{x+2}{x+1}-1 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{x^{2}-3x-7}{x^{2}-x-2}=\frac{x+2}{x+1}-1\) - step1: Find the domain: \(\frac{x^{2}-3x-7}{x^{2}-x-2}=\frac{x+2}{x+1}-1,x \in \left(-\infty,-1\right)\cup \left(-1,2\right)\cup \left(2,+\infty\right)\) - step2: Multiply both sides of the equation by LCD: \(\frac{x^{2}-3x-7}{x^{2}-x-2}\times \left(x+1\right)\left(x-2\right)=\left(\frac{x+2}{x+1}-1\right)\left(x+1\right)\left(x-2\right)\) - step3: Simplify the equation: \(x^{2}-3x-7=x-2\) - step4: Move the expression to the left side: \(x^{2}-3x-7-\left(x-2\right)=0\) - step5: Subtract the terms: \(x^{2}-4x-5=0\) - step6: Factor the expression: \(\left(x-5\right)\left(x+1\right)=0\) - step7: Separate into possible cases: \(\begin{align}&x-5=0\\&x+1=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=5\\&x=-1\end{align}\) - step9: Check if the solution is in the defined range: \(\begin{align}&x=5\\&x=-1\end{align},x \in \left(-\infty,-1\right)\cup \left(-1,2\right)\cup \left(2,+\infty\right)\) - step10: Find the intersection: \(x=5\) Solve the equation \( \\frac{2}{x}-\\frac{x+1}{x+2}=1 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{2}{x}-\frac{x+1}{x+2}=1\) - step1: Find the domain: \(\frac{2}{x}-\frac{x+1}{x+2}=1,x \in \left(-\infty,-2\right)\cup \left(-2,0\right)\cup \left(0,+\infty\right)\) - step2: Multiply both sides of the equation by LCD: \(\left(\frac{2}{x}-\frac{x+1}{x+2}\right)x\left(x+2\right)=1\times x\left(x+2\right)\) - step3: Simplify the equation: \(x+4-x^{2}=x^{2}+2x\) - step4: Move the expression to the left side: \(x+4-x^{2}-\left(x^{2}+2x\right)=0\) - step5: Calculate: \(-x+4-2x^{2}=0\) - step6: Rewrite in standard form: \(-2x^{2}-x+4=0\) - step7: Multiply both sides: \(2x^{2}+x-4=0\) - step8: Solve using the quadratic formula: \(x=\frac{-1\pm \sqrt{1^{2}-4\times 2\left(-4\right)}}{2\times 2}\) - step9: Simplify the expression: \(x=\frac{-1\pm \sqrt{1^{2}-4\times 2\left(-4\right)}}{4}\) - step10: Simplify the expression: \(x=\frac{-1\pm \sqrt{33}}{4}\) - step11: Separate into possible cases: \(\begin{align}&x=\frac{-1+\sqrt{33}}{4}\\&x=\frac{-1-\sqrt{33}}{4}\end{align}\) - step12: Rewrite the fraction: \(\begin{align}&x=\frac{-1+\sqrt{33}}{4}\\&x=-\frac{1+\sqrt{33}}{4}\end{align}\) - step13: Check if the solution is in the defined range: \(\begin{align}&x=\frac{-1+\sqrt{33}}{4}\\&x=-\frac{1+\sqrt{33}}{4}\end{align},x \in \left(-\infty,-2\right)\cup \left(-2,0\right)\cup \left(0,+\infty\right)\) - step14: Find the intersection: \(\begin{align}&x=\frac{-1+\sqrt{33}}{4}\\&x=-\frac{1+\sqrt{33}}{4}\end{align}\) - step15: Rewrite: \(x_{1}=-\frac{1+\sqrt{33}}{4},x_{2}=\frac{-1+\sqrt{33}}{4}\) The solutions to the given equations are: 1. \( x-5=\frac{6}{x} \) has solutions \( x=-1 \) and \( x=6 \). 2. \( \frac{x^{2}-3x-7}{x^{2}-x-2}=\frac{x+2}{x+1}-1 \) has solution \( x=5 \). 3. \( \frac{2}{x}-\frac{x+1}{x+2}=1 \) has solutions \( x=-\frac{1+\sqrt{33}}{4} \) and \( x=\frac{-1+\sqrt{33}}{4} \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve the equations for \( x \), let's tackle them one by one. 1. \( x - 5 = \frac{6}{x} \) To eliminate the fraction, multiply both sides by \( x \): \[ x(x - 5) = 6 \] \[ x^2 - 5x - 6 = 0 \] Now, factor the quadratic: \[ (x - 6)(x + 1) = 0 \] Setting each factor to zero gives: \[ x - 6 = 0 \quad \Rightarrow \quad x = 6 \] \[ x + 1 = 0 \quad \Rightarrow \quad x = -1 \] So, the solutions are \( x = 6 \) and \( x = -1 \). --- 2. \( \frac{x^{2}-3x-7}{x^{2}-x-2} = \frac{x+2}{x+1} - 1 \) Start by simplifying the right side: \[ \frac{x+2}{x+1} - 1 = \frac{x+2 - (x + 1)}{x + 1} = \frac{1}{x + 1} \] Now the equation becomes: \[ \frac{x^{2}-3x-7}{x^{2}-x-2} = \frac{1}{x+1} \] Cross-multiply: \[ (x^{2}-3x-7)(x+1) = x^{2}-x-2 \] Expanding the left-hand side gives: \[ x^3 - 2x^2 - 10x - 7 = x^{2}-x-2 \] Now bring all terms to one side: \[ x^3 - 3x^2 - 9x - 5 = 0 \] This cubic equation can be solved using methods like synthetic division or numerical methods. --- 3. \( \frac{2}{x} - \frac{x+1}{x+2} = 1 \) Start by finding a common denominator for the left side, which is \( x(x+2) \): \[ \frac{2(x+2) - (x+1)x}{x(x+2)} = 1 \] Simplify the numerator: \[ 2x + 4 - (x^2 + x) = 1 \] Combine like terms: \[ -x^2 + x + 4 = 1 \] Rearranging, we have: \[ -x^2 + x + 3 = 0 \] Multiplying through by -1 for simplicity gives: \[ x^2 - x - 3 = 0 \] Using the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): \[ x = \frac{1 \pm \sqrt{1 + 12}}{2} = \frac{1 \pm \sqrt{13}}{2} \] Thus, the solutions are: \[ x = \frac{1 + \sqrt{13}}{2} \quad \text{and} \quad x = \frac{1 - \sqrt{13}}{2} \] To sum it up, we found \( x \) values of \( 6 \), \( -1 \), and two roots from the quadratic formula. Happy solving!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy